Software Defined IPv6 Network: A New Paradigm for Future Networking - Dawadi, Babu Ram; Rawat, Danda Bahadur; Joshi, Shashidhar R. (Journal of the Institute of Engineering, 2019)
Recent advancement in the field of Information and Communication Technology (ICT) has encouraged all stakeholders to move towards the new networking paradigm. Internet Protocol version 6 (IPv6) addressing, Software Defined Network (SDN) and Network Function Virtualization (NFV) are regarded as technologies for enhancing network efficiency and effectiveness. However, the technology migration becomes one of the central challenges for the stakeholders such as service providers, end users, and regulatory bodies. This is more challenging in case of developing countries due to lack of sufficient cost and skilled human resources. In this paper, we provide an overview and survey of SDN and IPv6 networking technologies, their benefits and future challenges. Then we introduce Software Defined IPv6 (SoDIP6) network as a next generation networking technologies and their unified approach of deployment over the Tier-3 ISPs of the developing nations that could help for speedy and smooth migration with optimized cost. The demonstrated superior features of SDN enabled IPv6 network from different perspectives with its contributions to green ICT are recognized as the networks of the future generation in the networking world.